Peningkatan Pengetahuan Petani melalui Pelatihan Pembuatan Pupuk Organik Cair di Desa Karangrejo, Gumukmas, Kabupaten Jember. - Sugeng Winarso; Rendy Anggriawan; Laily Mutmainnah; Tri Candra Setiawati (Universitas Muhammadiyah Surakarta, 2023)
The use of agrochemicals is still an option in terms of providing fast nutrition and increasing plant growth more efficiently to a certain extent. However, its continuous use results in a decrease in soil quality and soil fertility, which in turn causes the accumulation of heavy metal ions in plant tissues, and affects nutritional yields and food safety. The community service activities were carried out by the SBF (Soil Biodiversity and Fertility) team of the Jember University Soil Science study program in Karangrejo Village, Gumukmas District, Jember Regency. Field visits were conducted on farmers' fields to review, evaluate and discuss qualitative characteristics of soil properties. This service activity aims to increase understanding of sustainable soil fertility management and training in making liquid organic fertilizer based on a local bacterial consortium. The results of the activity showed that farmers' knowledge of the parameters of soil properties, especially pH, nutrients, and soil organic matter, was still minimal. The level of acidity (pH) of the soil determines the factors of production through the ease with which nutrients are absorbed by plants as well as the possibility of the presence of toxic elements that can interfere with plant growth. Knowledge of soil pH is needed in relation to nutrient management and liming. A deeper understanding of several parameters of soil properties, especially soil pH values, needs to be emphasized and followed up through mentoring activities. Mentoring activities as follow-up activities for farmer groups are carried out with the target output of liquid organic fertilizer products. Entrepreneurship training for farmer groups members also needs to be carried out to build an entrepreneurial spirit and added value from livestock products by farmers so that the farmer's household economy can sustainable.